Dental treatment and recommended management in patients at risk of infective endocarditis - Błochowiak, Katarzyna J. (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2019)
Infective endocarditis (IF) is found in high-risk groups with congenital or acquired cardiac defects. It is caused by episodes of short bacteraemia. The magnitude and duration of bacteraemia caused by dental procedures are decreased by using antibiotic prophylaxis (AP). The aim of this study is to describe and discuss all clinical implications related to IF and dental procedures, and AP before invasive dental procedures. Maintenance of optimal oral health and hygiene is more important than AP in decreasing the risk of IF. Routine daily activities are associated with a similar risk of bacteraemia. It is estimated that antibiotics use in dentistry may represent up to 10% of total antibiotics use, and the risk of developing bacterial resistance should be taken into account.